Guchang Zhixie Wan protects mice against dextran sulfate sodium-induced colitis through modulating the gut microbiota in colon. (5th October 2020) - Wang, Zheng; Liang, Yanni; Yu, Jingao; Zhang, Dongbo; Ren, Langlang; Zhang, Zhen; Liu, Yanru; Wu, Xue; Liu, Li; Tang, Zhishu
Abstract: Ethnopharmacological relevance: Guchang Zhixie Wan (GC) is a traditional Chinese patent medicine used in the treatment of colitis in clinical trials. Though the notable effect of GC on colitis, the concrete mechanism of GC remain elusive. Emerging evidence showed that the imbalances of inflammatory cytokines and gut microbiota were both closely related to the initiation and progression of colitis. Aim of the study: To elucidate the relationship between the protective effects of GC on colitis and gut microbiota. Materials and methods: Male Kunming (KM) mice were enrolled in our work to establish colitis model induced by dextran sulfate sodium (DSS). The colitis mice were randomly divided into different groups and treated orally with 125 mg/kg of sulfasalazine (positive control) and 25, 50, 100 mg/kg of GC for 7 days, respectively. Inflammation cytokines of IL-1β, IL-4, IL-6, IL-8, IL-11, IL-12 and TNF-α were detected by ELISA analysis and the histological changes were detected by H&E staining. Gut microbiota diversity was analyzed by 16S rDNA sequencing. Metagenomes analysis were also conducted to reflect the protective effects of GC on colitis. Results: The results of CAS (Clinical Activity Score) confirmed the protective effects of GC on colitis. After administration of GC, the levels of pro-inflammatory cytokines IL-1β, IL-6, IL-8, IL-11, IL-12 and TNF-α were all decreased while the anti-inflammatory cytokines IL-4 was slightly increased, indicating that GC could down regulate pro-inflammatory cytokines. H&E staining revealed that GC could improve the histopathological structure of the colon tissue. The results of 16S rDNA sequences analysis showed that GC could decrease the relative abundance of Turicibacter and increase the relative abundance of Ruminococcaceae_UCG-005 . Conclusion: GC greatly improve the health condition of colitis mice induced by DSS through improving the imbalances of inflammatory cytokines and gut microbiota. Graphical abstract: Image 1